The impact of renewable and non-renewable energy consumption on economic growth: A global perspective with developed and developing economies - Muhammad Tariq Majeed; Awais Anwar; Tania Luni (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
This paper investigates the impacts of renewable and non-renewable energy consumption on economic growth employing a global panel data of 174 economies including the subsamples of developed and developing countries over the time 1980-2019. The renewable energy sources are disaggregated according to their source of production (biomass, solar, wind, and hydro) and their separate impacts on economic growth are estimated. The empirical exercise is based on the fixed effects, random effects, and two-step system GMM estimation approaches. The results reveal that renewable energy consumption exerts a positive influence on global economic prosperity including developed and developing countries. However, non-renewable energy boosts economic growth only in developing countries, while it retards growth in the developed world. The results reveal that alternative renewable energy sources have diverse implications for global growth management policies. On the one hand, biomass and solar energy resources stimulate global growth robustly while, on the other hand, hydro and wind energy sources exert mixed influences on economic growth. The gross capital formation increases while population growth reduces economic growth. Inflation boosts growth in developed economies while reduces in developing economies. For sustainable growth, the use of renewables should be promoted to preserve the environment.
Keywords: 330; renewable energy consumption; non-renewable energy consumption; economicgrowth; gross fixed capital formation; biomass; solar energy; hydro energy; wind energy